Select and accept - Matos, Maria Cristina Peixoto (2014)
The aim of this paper is to present how to solve the problem of selecting a candidate up to his or her acceptance trough game theory. The originality this paper proposes is how this problem will be approached. It will be treated as a single game which is made up of two parts, going as far as to state that the payoffs in the first part of the game will be the mediators of the second part of the game. In order to represent the problem described above, a new form of game representation will be used – code form – consisting of a table which contains all of the information, without any suppression or “adulteration” with regards to the game.